Pharmacokinetics, pharmacodynamics and bioavailability of dexmedetomidine nasal spray in healthy Chinese adults: A phase I clinical trial - Li, Yan; Qi, Lu; Wang, Zhenyu; Wang, Wan; Zhang, Langxi; Yang, Leting; Liu, Chen; Zhong, Wenjing; Wang, Xinghe (Frontiers in Pharmacology, 2024)
Background: Intranasal administration is a convenient route for drug delivery that can be applied for procedural sedation. However, there is currently limited exploration into fixed dosing regimens. This study was to investigate the pharmacokinetics (PK), pharmacodynamics (PD), bioavailability (BA) and safety of dexmedetomidine after fixed doses of intranasal and intravenous administration in healthy male and female subjects. Methods: Group A subjects received intranasal or intravenous administration in two periods (12 subjects received intranasal dexmedetomidine (Dex) or the intravenous formulation, and 4 received the corresponding placebo). Groups B to F underwent single-period dose ascending, receiving only the intranasal Dex formulation or the corresponding placebo (the number of subjects receiving the drug/placebo in groups B to F were 12/2, 12/2, 12/2, 10/2, 10/2, respectively), with doses of 75 μg, 125 μg, 150 μg, 175 μg, and 200 μg, respectively. After administration of each group, blood samples were collected to investigate the plasma concentration of dexmedetomidine, adrenaline and noradrenaline using a HPLC-MS/MS method. Ramsay score, blood pressure and heart rate were collected for safety evaluation. Pharmacokinetic parameters (Cmax, Tmax, AUC0-24h, AUC0-∞, and t1/2) of dexmedetomidine were calculated.Results:A total of 82 subjects were randomized. One subject withdrew for personal reasons before administration and the other subjects completed the entire study process. At a dose of 25 μg, the absolute bioavailability was 59%. Across the dose range of 25 to 200 μg, the median Tmax was similar (0.5 to 1 hour), and the mean elimination half-life was comparable (3.09 to 4.28 hours), with exposure (Cmax and AUC0-t) increasing with dose. The pharmacokinetics after intranasal spray administration exhibited linear characteristics, although Cmax was similar in the higher dose groups (175 μg and 200 μg). PD results showed that ideal sedation effects (Ramsay score of 3 or higher in at least 90% of subjects) could be achieved within 30 minutes following intranasal administration of 75 μg or higher doses. All the subjects were well tolerated without any serious adverse events (SAEs).Conclusions: Dexmedetomidine nasal spray was well tolerated and achieved satisfactory sedation in the dose range of 25-200 μg in Chinese healthy male and female subjects.